Diagnostic value of fine needle aspiration biopsy in parotid gland neoplasm - Yegin, Yakup; Çelik, Mustafa; Olgun, Burak; Simsek, Baver Masallah; Kayhan, Fatma Tulin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: The value of fine needle aspiration biopsy (FNAB) in the diagnosis of parotid masses remains unclear, considering current literature. The surgical procedure is not planned according to the FNAB results by the majority of the otorhinolaryngologists. Objectives of the study was to compare the results of FNAB and histopathological results in diagnosing malignancy and benign lesions of parotid gland and to determine the sensitivity, specificity and accuracy of FNAB. Methods: It is a retrospective clinical chart review study. In total, 61 patients (28 females and 33 males; average age, 46.31±15.79 years; age range: 12-82 years) with parotid gland masses who underwent preoperative FNAB were included in this study. All patients underwent FNAB under ultrasound guidance following clinical examination. Histopathological results of the surgical specimens and preoperative results of FNAB were compared and, the sensitivity, specify, positive predictive value (PPV), negative predictive value (NPV), the diagnostic accuracy of FNAB was calculated. A P-value <0.05 was considered to reflect statistical significance. Results: The specificity of FNAB was 100% and its sensitivity was 57.2%. Accuracy for benign lesion was 91.4%, accuracy for a malignancy was 42.8% and overall diagnostic accuracy was 92.0%, respectively. PPV for benign lesion was 91.4% and the NPV was 100%, respectively. PPV for malignancy was 100% and the NPV was 91.4%, respectively. Conclusions: We suggest that FNAB is a valid, safe, easy-to-use method for identifying of parotid gland neoplasms. We recommend FNAB for all potential surgical patients. In our opinion, good collaboration between the Otorhinolaryngologist and the pathologist provides the best results.